Ethanol sclerotherapy for management of endometriomas: an overview of systematic reviews - Younis, Johnny S.; Shapso, Nora; Izhaki, Ido; Taylor, Hugh S. (Frontiers in Endocrinology, 2025)
BackgroundEvidence suggests that endometrioma cystectomy can significantly reduce ovarian reserve. Ethanol sclerotherapy is a promising, minimally invasive alternative. This overview aims to critically evaluate systematic reviews that addressed the safety and efficacy of ethanol sclerotherapy in women with endometrioma and compared it to endometriotic cystectomy.MethodsA systematic search was conducted on PubMed, Medline, Epistemonikos, the Cochrane Library, and PROSPERO using the search terms “endometriosis OR endometrioma AND sclerotherapy.” Key outcomes assessed included adverse events, technical efficacy, pain relief, endometrioma recurrence, impact on ovarian reserve, ART success, and pregnancy outcomes. Two independent reviewers screened, reviewed, and selected relevant publications. They also evaluated the quality of the included systematic reviews using the modified version of the Assessing the Methodological Quality of Systematic Reviews (AMSTAR2) tool. Furthermore, they assessed the strength of evidence for the primary outcome measures according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. The study protocol was registered in advance at PROSPERO under registration number CRD42024595209 on 10 October 2024.ResultsNine systematic reviews were eligible, analyzing between 386 and 1,642 procedures. The reviews reported high technical efficacy (95.0%-98.3%) and low adverse events (11.0%-12.0% minor, 1.0%-1.7% major). Outcomes for pain relief, ovarian reserve, and pregnancy rates were generally favorable. Pregnancy rates for ethanol sclerotherapy and endometriotic cystectomy appeared comparable; however, sclerotherapy resulted in larger number of eggs retrieved and no loss of ovarian reserve. Overall, the strength of evidence for sclerotherapy was low to very low. though larger sample sizes supported findings on technical efficacy and adverse events.ConclusionsEthanol sclerotherapy is a viable alternative to endometriotic cystectomy for treating endometrioma in reproductive-age women. It has the advantage of being safe and effective for pain relief and potentially superior to cystectomy in preserving ovarian reserve. Future studies should evaluate sclerotherapy compared to cystectomy and expectant management in randomized controlled trials.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024595209.